2019
DOI: 10.3389/fpls.2019.00907
|View full text |Cite|
|
Sign up to set email alerts
|

The Conservation of VIT1-Dependent Iron Distribution in Seeds

Abstract: One third of people suffer from anemia, with iron (Fe) deficiency being the most common reason. The human diet includes seeds of staple crops, which contain Fe that is poorly bioavailable. One reason for low bioavailability is that these seeds store Fe in cellular compartments that also contain antinutrients, such as phytate. Thus, several studies have focused on decreasing phytate concentrations. In theory, as an alternative approach, Fe reserves might be directed to cellular compartments that are free of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…In the case of Plasmodium parasites, VIT1 plays a major role in iron detoxification during infection and is considered as a potential target for anti-malaria drugs [48] . VIT1 protein sequences within group V share high similarity through the plant kingdom and are responsible for iron accumulation around the provasculature in seeds [49] . However, plant VIT1 homologs have experimented functional divergence.…”
Section: Ccc1/vit1 Family Structure and Functionmentioning
confidence: 99%
“…In the case of Plasmodium parasites, VIT1 plays a major role in iron detoxification during infection and is considered as a potential target for anti-malaria drugs [48] . VIT1 protein sequences within group V share high similarity through the plant kingdom and are responsible for iron accumulation around the provasculature in seeds [49] . However, plant VIT1 homologs have experimented functional divergence.…”
Section: Ccc1/vit1 Family Structure and Functionmentioning
confidence: 99%
“…However, vacuolar sequestration of Fe represents an important cellular iron homeostasis mechanism in most plants (Ravet et al, 2009). Recently, analysis of accumulation of Fe in seeds in 21 distinct plant lineages revealed that Vacuolar Iron Transporter (VIT) mediated vacuolar Fe accumulation is widely conserved in plant kingdom (Eroglu et al, 2019). Not only in seeds, but recent reports also highlight the important role of VIT and VIT‐Like (VTL) genes in Fe transport during symbiotic nitrogen fixation (SNF) in legumes, which suggest universal role of these transporters in Fe transport and homeostasis within the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…In beans (Phaseolus vulgaris), Fe stores also concentrates around vascular tissues 86 . Recently, this observation was extended to Brassicales and even Rosids, which represent a wide group including a third of the angiosperms 87,88 . However, in many cases the number of cell layers that accumulate Fe is increased, to 2, the endodermis and one cortical cell layer in Brassicales, or even more cortical cell layers in other Rosids, compared to endodermis only in Arabidopsis 83,87,88 .…”
Section: Iron Storage In Seedsmentioning
confidence: 86%
“…However, in many cases the number of cell layers that accumulate Fe is increased, to 2, the endodermis and one cortical cell layer in Brassicales, or even more cortical cell layers in other Rosids, compared to endodermis only in Arabidopsis 83,87,88 . While screening representatives of the different groups of angiosperm, interesting exceptions were identified in Chenopodium quinoa and Carica papaya 87,88 . There are certainly more diverse patterns to be discovered.…”
Section: Iron Storage In Seedsmentioning
confidence: 99%